The impact of video-based virtual reality training on critical thinking and cognitive load - Al-Said, Khaleel; Berestova, Anna; Ismailova, Nailya; Pronkin, Nikolay (Institute of Advanced Engineering and Science, 2024)
Online learning, including in higher education, is an active part of the modern educational landscape. Spherical video-based immersive virtual reality (SV-IVR) is useful in this field. This study aimed to determine the impact of teaching with the use of SV-IVR on the critical thinking and cognitive load of 140 students. The findings of the study revealed that students exhibited low levels of mental effort and mental load based on the observed indicators. Compared to the traditional teaching method, the SV-IVR model had a better effect on improving students' critical thinking skills. The findings can help teachers develop new learning models using video-based virtual reality.